Analisis Keterlibatan Belajar (Learning Engagement) Peserta Didik Pada Materi Laju Reaksi di SMA IT Al-Mumtaz Pontianak - Erlina, Erlina; Zulaika, Aimi; Sahputra, Rachmat; Salam, Supriatno (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
Education plays a vital role in promoting students’ academic success, particularly in subjects that involve abstract and complex concepts such as reaction rates in chemistry. These concepts integrate macroscopic, microscopic, and symbolic aspects, which often lead to misconceptions when not properly understood. Therefore, students’ learning engagement encompassing behavioral, emotional, and cognitive dimensions is essential to foster meaningful understanding. This study aims to analyze the learning engagement of eleventh-grade students in the reaction rate topic at Integrated Islamic Senior High School Al-Mumtaz Pontianak during classroom learning activities. A descriptive qualitative approach was employed involving 18 students enrolled in the chemistry specialization for the 2024/2025 academic year. Data were collected through observation, interviews, and documentation. The findings reveal varied levels of engagement across the three dimensions. Behaviorally, students demonstrated active participation in academic tasks, although attendance consistency and adherence to classroom rules require improvement. Emotionally, students expressed enjoyment during the learning process, yet their specific interest in the reaction rate topic remains limited. Cognitively, students exhibited high motivation and initiative, particularly in collaborative learning contexts and through the use of diverse learning resources and strategies to enhance conceptual understanding. These findings emphasize the need to cultivate balanced engagement across behavioral, emotional, and cognitive domains to strengthen students’ conceptual mastery in chemistry learning.